2010
DOI: 10.1002/sia.3330
|View full text |Cite
|
Sign up to set email alerts
|

Femto‐ and attosecond electron dynamics in 5′‐Guanosine monophosphate interface as probed by resonant Auger spectroscopy

Abstract: To help in our understanding of the electron transport properties of deoxyribonucleic acid (DNA), it is useful to study the interfacial interaction between each nucleotide building block of DNA. Electron transfer properties between phosphate groups in microcrystalline 5 -Guanosin monophosphate (GMP) were probed using energy-dependent resonant Auger spectroscopy. Results show that the phosphate group of GMP forms an extended state along the phosphate directions similar to the case of DNA phosphate backbones. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A similar profile was obtained for previous studies on thiophene-based polymers. , The τ CT at 2472.6 eV photon energy corresponding to the T1 (S 1s → π* in the thiophene unit) transition is reduced 40% after the thermal annealing treatment at 200 °C. The other important difference observed between these exponential curves is their curve slopes, which may be dependent on the tunneling barrier and the density of delocalized states in the conduction band. , The curve slopes decrease with the thermal annealing treatment, which may reflect an increase in the density of delocalized states in the conduction band as a result of an increase in film ordering as reported by the S 1s NEXAFS analysis.…”
Section: Resultsmentioning
confidence: 96%
“…A similar profile was obtained for previous studies on thiophene-based polymers. , The τ CT at 2472.6 eV photon energy corresponding to the T1 (S 1s → π* in the thiophene unit) transition is reduced 40% after the thermal annealing treatment at 200 °C. The other important difference observed between these exponential curves is their curve slopes, which may be dependent on the tunneling barrier and the density of delocalized states in the conduction band. , The curve slopes decrease with the thermal annealing treatment, which may reflect an increase in the density of delocalized states in the conduction band as a result of an increase in film ordering as reported by the S 1s NEXAFS analysis.…”
Section: Resultsmentioning
confidence: 96%
“…The same experimental technique has been used to measure the femto-and attosecond electron dynamics in the 5′-guanosin monophosphate (GMP) nucleotide. 428 It was found that the electron delocalization time of the phosphate groups in GMP is faster than in DNA.…”
Section: Experimental Findingsmentioning
confidence: 99%
“…For wet DNA, the measured delocalization time is 740 ± 30 as at the excitation energy of 2153.7 eV, corresponding to a peak in the 2 h yield spectrum. The same experimental technique has been used to measure the femto- and attosecond electron dynamics in the 5′-guanosin monophosphate (GMP) nucleotide . It was found that the electron delocalization time of the phosphate groups in GMP is faster than in DNA.…”
Section: Toward Subfemtosecond Electron Dynamics In Biorelevant Molec...mentioning
confidence: 99%